Awakening from the European Dream: Eurimages and the Funding of Dystopia. Issue 1 (1st October 2015) - Power, Aidan
Abstract : Since its inception by the Council of Europe in 1989, Eurimages has been to the fore in financing European co-productions with the aim of fostering integration and cooperation in artistic and industry circles and has helped finance over 1, 600 feature films, animations and documentaries. Taking as its thesis the idea that the CoE seeks to perpetuate Europe's utopian ideals, despite the dystopian realities that frequently undermine both the EU and the continent at large, this article analyses select Eurimages-funded dystopian films from industrial, aesthetic and socio-cultural standpoints with a view toward decoding institutionally embedded critiques of the European project.